2007
DOI: 10.1080/00365520701396026
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the promoter region of theNFKB1gene increases the risk of sporadic colorectal cancer in Swedish but not in Chinese populations

Abstract: Deletion of the polymorphism was associated with increased susceptibility to sporadic colorectal cancers in the Swedish population, but not in the Swedish patients with a family history of colorectal cancer or in Chinese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…The first potential functional NFKB1 polymorphism is rs28362491 (-94 insertion/deletion ATTG), which is located between two putative key promoter regulatory elements. An increasing number of studies have reported an association between rs28362491 and cancer risk, although conflicting results have been obtained (Lewander et al, 2007;Cai et al, 2013;Li et al, 2013). Moreover, only one study reported that rs28362491 in NFKB1 was significantly associated with ovarian cancer (Huo et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…The first potential functional NFKB1 polymorphism is rs28362491 (-94 insertion/deletion ATTG), which is located between two putative key promoter regulatory elements. An increasing number of studies have reported an association between rs28362491 and cancer risk, although conflicting results have been obtained (Lewander et al, 2007;Cai et al, 2013;Li et al, 2013). Moreover, only one study reported that rs28362491 in NFKB1 was significantly associated with ovarian cancer (Huo et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Both the Swedish patients were males, diagnosed at 72 and 87 years of age, and had a heterozygote with a 4-bp aTTG deletion in the promoter region of the nFKB1 gene (4) and a heterozygote with a G→a variation in the 3' uTr of the nFKBia gene (5). The three chinese patients were all females diagnosed at 52, 57 and 69 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…data regarding the 4-bp aTTG polymorphism in the promoter region of the nFKB1 gene and the G→a variation in the 3' uTr of the nFKBia gene were taken from previous studies carried out at our laboratory (4,5). Table i presents the characteristics of the Swedish and chinese populations examined in the present study.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A genomic DNA sequence of 289 bp upstream of the NFKB1 gene was amplified using polymerase chain reaction with restriction fragment length polymorphism (PCR-RFLP), as described by Lewander et al [22]. PCR mixtures (20 ll) contained 50 ng of genomic DNA, 1 9 PCR buffer, 2.5 mM MgCl 2 , 0.25 mM dNTP, 0.5 mM of each primer and 0.5 U Taq polymerase (SDS Bioscience, São Paulo, Brazil).…”
Section: Genotyping Of Nfkb1 Polymorphismmentioning
confidence: 99%